2019
DOI: 10.1177/1362361319864804
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in self-reported camouflaging in autistic and non-autistic adults

Abstract: Social camouflaging describes the use of strategies to compensate for and mask autistic characteristics during social interactions. A newly developed self-reported measure of camouflaging (Camouflaging Autistic Traits Questionnaire) was used in an online survey to measure gender differences in autistic ( n = 306) and non-autistic adults ( n = 472) without intellectual disability for the first time. Controlling for age and autistic-like traits, an interaction between gender and diagnostic status was found: auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
185
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 209 publications
(214 citation statements)
references
References 39 publications
21
185
2
6
Order By: Relevance
“…rsfMRI H in autistic adults was also relevant in a sex-specific manner to a clinical behavioral phenomenon known as 'camouflaging'. Camouflaging relates to a set of compensatory or masking strategies or mechanisms that allows individuals to cope with their socialcommunicative difficulties in everyday social situations 16,17,45 . It is known that cognitively able adult autistic females tend to engage in more camouflaging behavior than males [16][17][18] and the extent to which individual females engage in camouflaging is linked to vMPFC function 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…rsfMRI H in autistic adults was also relevant in a sex-specific manner to a clinical behavioral phenomenon known as 'camouflaging'. Camouflaging relates to a set of compensatory or masking strategies or mechanisms that allows individuals to cope with their socialcommunicative difficulties in everyday social situations 16,17,45 . It is known that cognitively able adult autistic females tend to engage in more camouflaging behavior than males [16][17][18] and the extent to which individual females engage in camouflaging is linked to vMPFC function 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Camouflaging relates to a set of compensatory or masking strategies or mechanisms that allows individuals to cope with their socialcommunicative difficulties in everyday social situations 16,17,45 . It is known that cognitively able adult autistic females tend to engage in more camouflaging behavior than males [16][17][18] and the extent to which individual females engage in camouflaging is linked to vMPFC function 19 . One of the most important known functions of vMPFC has to do with self-representation 46 and simulating others based on information about the self 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassidy et al 2018 Score on four self-report questions of camouflaging Dean et al 2017 Observed social behaviours in the playground Hull et al 2017a Self-reported behavioural examples Hull et al 2018 Score on self-report measure of camouflaging behaviours (CAT-Q). Hull et al 2019 Score on self-report measure of camouflaging behaviours (CAT-Q).…”
Section: Discrepancy Approachmentioning
confidence: 99%